2014
DOI: 10.2528/pierm14102903
|View full text |Cite
|
Sign up to set email alerts
|

Review and Assessment of Electromagnetic Wave Propagation in Sand and Dust Storms at Microwave and Millimeter Wave Bands --- Part Ii

Abstract: Abstract-Suspended particles in the atmosphere during sand and dust storms have numerous consequences on electromagnetic wave propagation in arid regions. The electromagnetic wave signal may suffer attenuation and cross polarization upon encounter with the suspended particles. However, meager information has hitherto been reported about effect of storms on the telecommunication systems operating in such regions. This paper presents a survey of current understanding of the electromagnetic wave propagation in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…These phenomena are caused by the dispersion and absorption of the waves in the medium [10]. These two mechanisms are at the base of signal attenuation and strongly depend on the dielectric constant and the particles' size [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena are caused by the dispersion and absorption of the waves in the medium [10]. These two mechanisms are at the base of signal attenuation and strongly depend on the dielectric constant and the particles' size [11].…”
Section: Methodsmentioning
confidence: 99%
“…A few papers indicate, in the presence of air pollution, the possibility of a significant cross polarization of the electromagnetic waves, while none of the papers indicated the possibility of a significant attenuation [10][11][12][13]. This paper has tried to partially fill this gap of knowledge in this field with some new contributions.…”
Section: Methodsmentioning
confidence: 99%
“…[2] and [6] reviewed and assessed wave propagation in SDS. They presented a survey of the understanding of wave propagation during the SDS.…”
Section: Introductionmentioning
confidence: 99%
“…They presented a survey of the understanding of wave propagation during the SDS. [2] detailed the parametric assessment of some important properties affecting wave propagation in SDS, while [6] described the principle of approach and technology adopted for the investigation and established the gap in knowledge in the field. [5] calculated the attenuation of the electromagnetic waves in SDS using Mie theory.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is found that the attenuation of microwave and MMW signal by dust is not a serious problem except under very dense storms [3]. Investigation, modelling and research of the dusty channel in FSO links is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%